2005
DOI: 10.1242/jcs.02302
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule nucleation and anchoring at the centrosome are independent processes linked by ninein function

Abstract: Evidence that an interaction between EB1 and p150 Glued is required for the formation and maintenance of a radial microtubule array anchored at the centrosome. Mol. Biol. Cell 13, 3627-3645.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
288
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(319 citation statements)
references
References 53 publications
27
288
4
Order By: Relevance
“…In polarized cells, ninein is also found at noncentrosomal sites, and in neurons it has been implicated in the recapture and stabilization of free MT minus ends as the MTs translocate into developing neurites (Baird et al, 2004). There is evidence that ninein also has a role in MT nucleation and anchoring by providing a direct link between centrioles and ␥-TuRCs (Delgehyr et al, 2005).…”
Section: Generation Of Noncentrosomal Mtsmentioning
confidence: 99%
“…In polarized cells, ninein is also found at noncentrosomal sites, and in neurons it has been implicated in the recapture and stabilization of free MT minus ends as the MTs translocate into developing neurites (Baird et al, 2004). There is evidence that ninein also has a role in MT nucleation and anchoring by providing a direct link between centrioles and ␥-TuRCs (Delgehyr et al, 2005).…”
Section: Generation Of Noncentrosomal Mtsmentioning
confidence: 99%
“…In line with this, NIN, another gene associated with an SEMD-JL2-like phenotype, 8 encodes ninein required for centrosome maturation and architecture. 18 As building and maintenance of a cilium depend on membrane vesicle trafficking, microtubuledependent motor proteins and formation of basal bodies, 19 we speculate that dysfunction of EXOC6B, KIF22 and ninein negatively affects ciliogenesis leading to overlapping SEMD forms. EXOC6B nonsense variant in a novel SEMD type KM Girisha et al…”
Section: Resultsmentioning
confidence: 91%
“…Thus, as ninein, 14 nucleolin is involved in both microtubule nucleation and anchoring at the centrosome. Nucleolin could anchor microtubules directly or via other anchoring protein localizing at the mature centriole such as ninein 14 since nucleolin antibodies immunoprecipitated ninein, or through p150 glued , APC, FOP, CAP350 and EB1, [40][41][42] Kif3a, 43 nudel 44 or 4.1R-135. 45 Previous studies have shown the presence of extra centrosomes markers containing structure in mitotic cells silenced for nucleolin.…”
Section: Discussionmentioning
confidence: 99%
“…11 The distal appendages are important during ciliogenesis to anchor the mother centriole to the plasma membrane 12,13 whereas the subdistal appendages are involved in microtubule anchoring at the centrosome. 13,14 Even though, proteomic analyzes have identified several proteins associated with the centrosomes, 15,16 their localization within the centrosome structure has only been characterized for a subset of proteins. Development of super-resolution approaches in optics, have recently contributed to decipher internal centrosomal organization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation